Good Corporate Governance Principles in Islamic Banking: A Legal Perspective on the Integration of TARIF Values - Hirsanuddin, Hirsanuddin; Martini, Dwi (Journal of Indonesian Legal Studies, 2023)
Islamic banking, rooted in the foundational principles of shiddiq (honesty), tabligh, amanah (fulfillment of beliefs), and fatanah (intelligence) derived from the teachings of Prophet Muhammad, stands in stark contrast to conventional banking, which is driven by Western-derived concepts encapsulated in Good Corporate Governance (GCG). The latter is characterized by principles such as transparency, accountability, responsibility, independency, and fairness (TARIF). This research investigates the possibilities and implications of applying GCG principles in Islamic banking, examining their impact on Islamic economic law. Utilizing a normative legal study, the research delves into primary and secondary legal materials, employing a deductive analysis with both statutory and conceptual approaches. The integration of GCG principles in Islamic banking signifies a convergence of values that fosters justice, tawazun (balance), mas’uliyah (accountability), akhlaq (morality), shiddiq (honesty), amanah (fulfillment of beliefs), fatanah (intelligence), and economic equilibrium within the framework of Islamic economic law.